2016
DOI: 10.1080/14397595.2016.1220447
|View full text |Cite
|
Sign up to set email alerts
|

Cyr61 participates in the pathogenesis of rheumatoid arthritis via promoting MMP-3 expression by fibroblast-like synoviocytes

Abstract: This study provides new evidence that Cyr61 participates in RA pathogenesis not only as a pro-inflammatory factor but also plays a key role in bone erosion via promoting MMP-3 expression. We suggest that targeting of Cyr61 may represent a potential strategy in RA treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 29 publications
2
10
0
Order By: Relevance
“…In agreement with the proposal, treatment of mice that had collagen‐induced arthritis using a murine monoclonal antibody specifically targeting CCN1, namely, 093G9, led to amelioration of the inflammation reaction and down‐regulation of Th17 population, accompanied by both decreased IL‐6 production in synovial tissues and IL‐6R expression on the surface of T cells . In addition, CCN1 participates in the pathogenesis of RA via promotion of proIL‐1β production and MMP‐3 expression by FLS, and 093G9 is effective to antagonize the effects of CCN1 …”
Section: Introductionsupporting
confidence: 78%
See 4 more Smart Citations
“…In agreement with the proposal, treatment of mice that had collagen‐induced arthritis using a murine monoclonal antibody specifically targeting CCN1, namely, 093G9, led to amelioration of the inflammation reaction and down‐regulation of Th17 population, accompanied by both decreased IL‐6 production in synovial tissues and IL‐6R expression on the surface of T cells . In addition, CCN1 participates in the pathogenesis of RA via promotion of proIL‐1β production and MMP‐3 expression by FLS, and 093G9 is effective to antagonize the effects of CCN1 …”
Section: Introductionsupporting
confidence: 78%
“…Previously, we have demonstrated that 093G9 is effective to antagonize the function of CCN1 and has great potential for the treatment of RA . In this study, we mapped the CCN1 epitope for 093G9, which is located in the IGFBP domain of CCN1.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations